Efficacy of Pseudomonads as biocontrol agents of phytopathogens - Adel K. Madbouly (Novel Research in Microbiology Journal)
Microbial plant pathogens infecting different crops cause great economic losses worldwide. Thus plant diseases need to be controlled to maintain the quality and abundance of these crops. Different approaches have been used to control plant diseases, mainly chemical fertilizers and pesticides. However, environmental pollution and pathogens induced resistance due to excessive use of these agrochemicals; may exclude their successful application. Consequently, researchers have focused on developing alternatives to control plant diseases; among these alternatives is biological control. The term biological control or biocontrol applies to the use of living antagonists to suppress or kill deleterious plant pathogens. The saprophytic microbe which antagonises the pathogen is called the biological control agent (BCA) or bioagent. Microbe-mediated biological control is considered safe as being close to the natural ecosystems (Coleman-Derr and Tringe, 2014). There are two general ways of applying biocontrol agents against phytopathogens; through addition of large amounts of bioagents to the soil or stimulating the activities of the existing bioagents using various amendments (Conrath, 2011).